2003
DOI: 10.22621/cfn.v117i3.739
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Aspects of a Wood Turtle, <em>Glyptemys insculpta</em>, Population at the Northern Limit of its Range in Québec

Abstract: As part of a conservation research initiative, a population of Wood Turtles (Glyptemys insculpta) at the northern limit of its range was studied to ascertain characteristics of its demographics, morphometrics, density, mortality, feeding, and mating activities. Turtles were captured and marked during the activity period in 1996 and 1997. In addition, 20 individuals were radio-tracked weekly. A total of 188 turtles was captured and the size of the population in the study area was estimated at 238 turtles. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 48 publications
7
23
0
Order By: Relevance
“…At the northern limits of the species distribution in Ontario, census population size is approximately 238 turtles (Walde et al 2003). Our estimate of census population size in Iowa (77 turtles) is one of the lowest reported for a G. insculpta population to date, similar to that estimated for the species in Quebec (66 turtles; Daigle 1997).…”
Section: Population Size and Demographysupporting
confidence: 61%
See 1 more Smart Citation
“…At the northern limits of the species distribution in Ontario, census population size is approximately 238 turtles (Walde et al 2003). Our estimate of census population size in Iowa (77 turtles) is one of the lowest reported for a G. insculpta population to date, similar to that estimated for the species in Quebec (66 turtles; Daigle 1997).…”
Section: Population Size and Demographysupporting
confidence: 61%
“…Wood turtle population size is suppressed by habitat fragmentation due to agriculture and urban development, injury from agricultural practices and vehicle traffic, and collection for the pet trade Bider 1998, 2007;Levell 2000;Gibbs and Shriver 2002;Walde et al 2003;Ernst and Lovich 2009). Agricultural practices are associated with reduced juvenile prevalence (Saumure and Bider 1998) and appear, in Iowa, to benefit raccoon and skunk populations (Kuehl and Clark 2002), which are major predators of wood turtle eggs and juveniles (Harding 2008;Ernst and Lovich 2009).…”
Section: Detriments To Recruitmentmentioning
confidence: 99%
“…Our population estimates (20-32 turtles km -1 ), however, are well within the range of other studies that have reported population estimates per river km (Walde et al, 2003;Daigle and Jutras, 2005;Brown et al, 2017; Table 1). Willoughby et al (2013) reported evidence of a historical decline in this population of Wood Turtles using genetic data and a coalescent theory model (MSVar).…”
Section: Discussionsupporting
confidence: 87%
“…However, studies on other aquatic species, which may be expected to show the same patterns of size and shape dimorphism as C. picta, have found that females are more likely to be killed by predators than males (Emmons, 1989;Gibbons and Lovich, 1990;Shealy, 1976), although these are also species in which females probably encounter more predators than males. In addition, previous studies have also found that female turtles show proportionally more injuries than males in some species, including G. insculpta (Ernst, 1976;Walde et al, 2003). These studies may suggest that females encounter more predators than males, or they may actually provide support for the idea that female turtles are better able to withstand predator attacks-the lower incidence of injuries among males may indicate that their encounters with predators more often end in death rather than injury.…”
Section: Resultsmentioning
confidence: 72%